Ambient temperature deposition of gallium nitride/gallium oxynitride from a deep eutectic electrolyte, under potential control. Issue 38 (13th April 2016) - Sarkar, Sujoy; Sampath, S.
Abstract : A ternary, ionically conducting, deep eutectic solvent based on acetamide, urea and gallium nitrate is reported for the electrodeposition of gallium nitride/gallium indium nitride under ambient conditions; blue and white light emitting photoluminescent deposits are obtained under potential control. Abstract : A ternary, ionically conducting, deep eutectic solvent based on acetamide, urea and gallium nitrate is reported for the electrodeposition of gallium nitride/gallium indium nitride under ambient conditions; blue and white light emitting photoluminescent deposits are obtained under potential control.